10. The Sperm Quality of Diabetic Rat (Rattus norvegicus) After Treated with Bitter Melon (Momordica charantia L.) Extract - Elsa Suarni; Dasrul Dasrul; Triva Murtina Lubis; Azhar Azhar; Rinidar Rinidar; Ismail Ismail (Jurnal Medika Veterinaria, 2020)
The purpose of this study was to determine the sperm quality of  diabetic  rat (Rattus norvegicus) after treated with bitter melon (Momordica charantia L.) extracts. This study followed direct complete randomized design using 15 male rats (Rattus norvegicus) Wistar’s strain which divided into 3 groups. group I (K1) as a control, group II (K2) was diabetic rat  which induced 120mg / kg bw alloxan intraperitoneally, and group III (K3) was diabetic rat which treated with 100mg / kg bw extract of bitter melon, Examination of sperm count, motility, and sperm abnormality was checked at day 48. Data sperm count, motility, and sperm abnormalities was analyzed using ANOVA and Duncan multiple test. The results showed that administration of bitter melon extract dose  100 mg / kg bw for 48 days can improve count and motility spermatozoa (P0,05) and decrease abnormalities of spermatozoa (P0,05).   Bitter melon fruit extract dose  100 mg / kg bw can prevent decrease  sperm quality of diabetic rats